Job Creation Potential for the Youth and Challenges in the Agricultural Industry - 마상진 (한국농촌경제연구원, 2017)
 The job creation potential in the agricultural industry is higher than any other industries in Korea. – The agricultural industry has a lower labor productivity than other industries, but creates a better employment effect given investment when the unemployment rate is extremely low due to an economic slump. The economic scale of the industry based on the gross output is KRW 320 trillion (8.9% of the entire industrial sector), with 3.96 million employees engaged (17.1% of the number of employees in the entire industrial sector) (The Bank of Korea, 2016). The coefficient of employment (the number of employees per KRW 1 billion of output) is 12.4, twice the average (6.4) of the entire industrial sector. – Considering the forecast of agricultural workers in the future and the current employees to retire in the near future, about 1.16 million new workers will be needed in 2023 (based on the data of 2013): to be specific, 610,000 in agricultural/forestry production, 340,000 in food service, 98,000 in agricultural/forestry food processing, 29,000 in agricultural/forestry service, 5,000 in agricultural/forestry inputs, and 80,000 in agricultural/forestry distribution. This forecast shows a potential for job creation in the sector.  Despite the interest of the youth (agricultural high school and college students and those with non-agricultural majors) in working in the agricultural sector in the future, there are not sufficient information and training opportunities for them. – According to the survey of agricultural high school and college students and those with other majors about their plans for future career, 42.2% of agricultural high school students, 73.8% of agricultural college students, and 30.4% of those with non-agricultural majors are interested in working in the agricultural industry after graduation. – When asked about difficulties in seeking jobs or starting a new business in the agricultural industry, a large percentage of the respondents pointed out the lack of job opening information, relevant knowledge and techniques, and experience.  In order to boost youth employment in the agricultural sector, it is necessary to improve the quality of jobs, strengthen industry-academic cooperation between agricultural enterprises and schools, and establish a policy implementation framework to support such activities. – The wage support and welfare system should be improved to enhance the quality of jobs in the agricultural industry. To this end, the central and local governments and institutions of each subcategory should make concerted efforts. If necessary, the basic income guarantee system can be applied first to young people who want to enter the agricultural industry. – Youth employment can be accelerated by elaborating the policy regarding the intermediate phase between school and the labor market. Various policies are urgently needed for those who fail in moving on to the labor market after graduation. In particular, industry-academic partnerships should be promoted between agricultural schools and the agricultural job market. – At the Ministry of Agriculture, Food and Rural Affairs, a division in charge of employment in the agricultural industry should be newly organized to systematically implement policies that encompass the education, development, supply and utilization of human resources in the industry. Relevant statistics and job information sharing systems should be reorganized. Furthermore, it is also needed to invigorate the public-private governance for boosting employment in the agricultural industry in each region and intermediate groups for supporting education and training of each subcategory of the sector.